(3TQM aUhd GdCMcGe hHjGf eG eVi Hg GdYed YfO GdabgGAs - (3SdjeGf Hf Nda Hf SYO GdJLjHj GdbQWHj, CHh GdhdjO GdHGLj,J (B474 (3g` s
(3ChdgG (B:s
(3jHOC HaUd ef HjGf eG ChLHg Gddg JYGdi Ydi GdfGS ai GdbjGe HGdbSW s
(3BNQgG (B:s
(3jfJgi HaUd ai HjGf CMcGe GdOeGA hGdLfGjGJ s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B125 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B261s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B193s
Keywords: (3Gdabg GdeGdcjs